NUMERICAL SIMULATION OF WATER CIRCULATION IN A CYLINDRICAL HORIZONTAL THERMAL TANK - Savicki, D. L.; Vielmo, H. A. (Revista de Engenharia Térmica, 2009)
It is carried out a numerical study of the three-dimensional temperature and velocity fields in a cylindrical horizontal thermal tank during the process of water circulation. The numerical simulations were made using an academic Finite Volumes numerical code. This simulation considers that the thermal tank is connected to solar collectors. So, in the tank, the inlet jet temperature is higher than those inside the tank. This study aims to investigate the influence of the inlet jet on thermal stratification. The results show that for the mass flow rate studied, there is no significant variation on thermal stratification.